Hubungan Pemberian Ekstrak Cordyline fruticosa L.A Cheval Terhadap Penurunan Kolesterol Tikus Putih - Rahmawati, Dian (Jurnal Farmasi Udayana, 2020)
ABSTRACT This study aims to determine the effect of ethanol extract of cordyline fruticose leaves in reducing total cholesterol levels of male white rats. This study used 30 male white rats which were divided into 6 treatment groups, each groups consistent of 5 test animals. Group I was normal control, group II was negative control (High cholesterol died and streptozotocin 30 mg/kgBW, group III was positive control (Simvastatin suspension), group IV, V, VI were each given an ethanol extract of cordyline fruticose leaves at a dose of 100 mg/kgBW, 150 mg/kgBW and 200 mg/kgBW for 14 consecutive days. Measurements of analyzed using a one-way statistical test (ANOVA) at 95% confidence level and continued with the Least Significant Difference (LSD) test to analyze differences between the groups. The result showed that the ethanol extract of cordyline fruticose leaves at a dose 200 mg/kgBW was able to reduce total cholesterol levels in white rats with cholesterol level of 39 mg/dL. Keywords :  High fat feed, Cordyline fruticosa, Cholesterol .